Tomasz Bazylewicz, Łukasz Hajdrych (red.), Gra w historię, historia w grach, Instytut Historii Uniwersytetu im. Adama Mickiewicza, Poznań 2018, ss. 161 - Kaźmierska, Marlena (Studia Edukacyjne, 2020)
Tomasz Bazylewicz, Łukasz Hajdrych (red.), Gra w historię, historia w grach, Instytut Historii Uniwersytetu im. Adama Mickiewicza, Poznań 2018, ss. 161